Measuring medical graduate behavioral intention for administering on-site care to road traffic accident victims: Development and validation of a questionnaire - Neeti Rustagi; Abhishek Jaiswal; Dervla Kelly; Naveen Dutt; Arvind Sinha; Pankaja Raghav (Wolters Kluwer Medknow Publications, 2021)
Background: Prehospital trauma care skills are often taught and assessed in undergraduate medical curricula but the intention to voluntarily offer these skills in out of hospital or primary care settings is poorly understood. Objectives: The objective is to develop and validate a questionnaire measuring behavioral intention among medical graduates for administering on-site care to road accident victims. Methods: A cross-sectional study was conducted from September 2018 to February 2019, among medical graduates of an academic institution in Jodhpur, Rajasthan. Items for "Measure of Intention to help road accident victim (MIHRAV) instrument" were framed as per the constructs of theory of planned behavior. A total of 150 candidates undergoing internship were approached for informed consent and a link for online questionnaire was shared. Statistical Analysis: Exploratory factor analysis (EFA) and tests for convergent, discriminant, and predictive validity was done using IBM SPSS version 23.0 for psychometric validation of scale. Results: Original version of MIHRAV included 29 items which were reduced to 18 items. EFA identified five factors which explained 72% of cumulative variance with high Cronbach's α (0.920). Discriminant validity showed adequate correlations ranging from 0.283 to 0.541. Predictive validity demonstrated that model was significantly able to predict "behavioural intention to help" (F (4128) = 24.139, P = 0.0001) and explained 43% of variance. Conclusion: The findings reveal that developed instrument "MIHRAV" is a reliable and valid scale for predicting behavioral intention among medical graduates for administering onsite care to road accident victims.